FIELD PERFORMANCE OF BAU-STR DRYER IN RURAL AREA OF BANGLADESH - Alam, Md. Ashraful; Saha, Chayan Kumer; Alam, Md. Monjurul (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
Paddy drying after harvest is important for reducing loss and storing long term. High moisture promotes the development of insects and molds that are harmful to the grain. It is necessary to adapt technology for drying paddy at small scale traders and farmersâ level as an alternative to traditional sun drying. The low cost BAU-STR dryer would be one of the alternative effective drying technologies. Therefore, the objective of this study was to investigate technical and financial performance of BAU-STR dryer at the field level. The study of BAU-STR dryer was conducted during Boro Season, 2016 at selected areas of Mymensingh and Jessore districts. Air temperature inside grain bin was recorded using 3 ACR Smart Button data logger. Ambient air temperature was recorded using TRH-1000 sensor. Moisture content of the grain was measured at five locations in the BAU-STR dryer during drying operation. The dryer was evaluated with three verities: T1-SL 8, T2-Hybrid Taj, T3-BRRI dhan28 which consider as three treatments. The dryer capacity was 500 kg per batch. The results showed that the temperature and moisture distributions in BAU-STR dryer were uniform. Paddy was dried from moisture content 22.8 to 12.2% uniformly in between 2.5 to 4.8 hours for 500 kg dryer capacity in different treatments. The drying time for larger grain (T1-SL8) was less compared to other two varieties. The drying efficiency was about 52%, 65% and 52% for T1, T2, and T3, respectively. The operating cost of drying was found Tk. 0.87 per kg (diesel engine operated blower) for BAU-STR dryer. The benefit-cost ratio and payback period were found 1.9 and 0.28 yr for diesel engine operated BAU-STR dryer from the experiments at field level of Bangladesh.